3D vs. turbostratic: controlling metal–organic framework dimensionality via N-heterocyclic carbene chemistry. Issue 21 (17th May 2022) - Kochetygov, Ilia; Justin, Anita; Asgari, Mehrdad; Yang, Shuliang; Karve, Vikram; Schertenleib, Till; Stoian, Dragos; Oveisi, Emad; Mensi, Mounir; Queen, Wendy L.
Abstract : A new MOF with a saturated N -heterocyclic carbene ligand undergoes a series of structural transformations to produce a turbostratic material, which serves as a better support for an iridium hydrogenation catalyst, when compared to the parent material. Abstract : Using azolium-based ligands for the construction of metal–organic frameworks (MOFs) is a viable strategy to immobilize catalytically active N -heterocyclic carbenes (NHC) or NHC-derived species inside MOF pores. Thus, in the present work, a novel copper MOF referred to as Cu-Sp5-BF4, is constructed using an imidazolinium ligand, H2 Sp5-BF4, 1, 3-bis(4-carboxyphenyl)-4, 5-dihydro-1 H -imidazole-3-ium tetrafluoroborate. The resulting framework, which offers large pore apertures, enables the post-synthetic modification of the C 2 carbon on the ligand backbone with methoxide units. A combination of X-ray diffraction (XRD), solid-state nuclear magnetic resonance (ssNMR) and electron microscopy (EM), are used to show that the post-synthetic methoxide modification alters the dimensionality of the material, forming a turbostratic phase, an event that further improves the accessibility of the NHC sites promoting a second modification step that is carried out via grafting iridium to the NHC. A combination of X-ray absorption spectroscopy (XAS) and X-ray photoelectron spectroscopy (XPS) methods are used to shed light on the iridium speciation, and the catalytic activity of the Ir–NHC containing MOF is demonstrated using a model reaction, stilbene hydrogenation.